A novel multifunctional polymer ionic liquid as an additive in iodide electrolyte combined with silver mirror coating counter electrodes for quasi-solid-state dye-sensitized solar cells. Issue 8 (1st February 2021) - Lin, Fang-Sian; Sakthivel, Mani; Fan, Miao-Syuan; Lin, Jiang-Jen; Jeng, Ru-Jong; Ho, Kuo-Chuan
Abstract : A novel multifunctional polymer ionic liquid poly(oxyethylene)-imide-2, 2, 6, 6-tetramethyl-1-piperidinyloxy (POEI-TEMPO ) was successfully prepared and used as an additive in iodide electrolyte in quasi-solid-state dye-sensitized solar cells (QSS-DSSCs). Abstract : A novel multifunctional polymer ionic liquid poly(oxyethylene)-imide-2, 2, 6, 6-tetramethyl-1-piperidinyloxy (POEI-TEMPO ) was successfully prepared and used as an additive in iodide electrolyte in quasi-solid-state dye-sensitized solar cells (QSS-DSSCs). The POEI segment in the electrolyte has good mechanical strength; meanwhile, the TEMPO organic radical contains nitroxide as the redox couple (RN-O˙/RNO + ) acting as a superior mediator in DSSCs. TEMPO has a number of favorable properties, such as fast and reversible redox kinetics, large apparent diffusion coefficient ( D app ), positive redox potential, and facile electron self-exchange reaction. As a result, DSSCs were composed of a POEI-TEMPO /iodide electrolyte and a Pt-coated FTO layer on glass as a normal counter electrode (PtCE), whereas the other side of the glass was coated with silver mirror coating (SMC) as the bifacial PtCE/SMC cell. DSSC exhibited a maximum photoelectric conversion efficiency ( η ) of 9.83%, open-circuit voltage ( V OC ) of 812.84 mV, and short-circuit current density ( J SC ) of 16.60 mA cm −2 under 1 sun (AM 1.5 G, 100 mW cm −2 ), whereas the value of η reached 25.99% under an indoor condition with 6000 lux (1.89 mW cm −2 ). Moreover, when POEI-TEMPO is used as an additive, the bifacial cell maintains its high performance with a reasonable long-term stability. The finding is expected to have a practical impact on harvesting the ambient light energy and extending the cell lifetime.